Association Between Preoperative Blood Glucose Level and Hospital Length of Stay in Patients With Kidney Stones Undergoing Percutaneous Nephrolithotomy - Sun, Si; Mao, Weipu; Tao, Shuchun; Wan, Lilin; Zou, Xiangyu; Zhang, Guangyuan; Chen, Ming (Frontiers in Surgery, 2022)
Aim To assess the effect of preoperative blood glucose (POBG) levels on the length of stay (LOS) in patients with kidney stones undergoing percutaneous nephrolithotomy (PCNL). Methods We conducted a retrospective study of patients who underwent PCNL at the Zhongda Hospital of Southeast University from 2013 to 2019. The relationship between POBG level and LOS was investigated by dose-response analysis curves of restricted cubic spline function. Results We included 310 patients and divided them into three groups (<5.04 mmol/L, 5.04 to <6.88 mmol/L, ≥6.88mmol/L) according to the POBG levels. Patients with POBG levels ≥6.88 mmol/L (adjusted odds risk [aOR]1.67; 95% CI 0.83-3.33) had a 67% higher risk of LOS >two weeks than patients with POBG levels <5.04 mmol/L. A positive dose-response analysis curve was observed between POBG and the adjusted risk of LOS >two weeks. Similar results were observed in the subgroups analysis. Conclusion We demonstrated that higher POBG levels were significantly associated with longer LOS in patients with kidney stones undergoing PCNL. Keywords: Kidney stones; Length of stay; Percutaneous nephrolithotomy; Preoperative blood glucose; Retrospective study